Extraction and Characterization of Pectin from Mango (Mangifera indica L.) Peel Waste as a Hydrogel-Based Material - Irga Manta Sari Siregar; Muhammad Reza (UNIB Press, 2026)
Mango peel (Mangifera Indica L.) is an abundant agro – industrial biomass waste that may cause environmental impacts such as water pollution, greenhouse gas emissions, air pollution, and soil degradation if not properly utilized. This waste contains polysaccharides, particularly pectin, which can be processed into porous materials such as hydrogels for use as adsorbents. The water – soluble nature of pectin makes it an environmentally friendly material that does not contribute to persistent solid waste. This study aimed to extract pectin from mango peel waste using an acid extraction method with 0.1 M citric acid solution as the solvent. The extraction resulted in a pectin yield of 10%. FTIR characterization confirmed the presence of characteristic functional groups of pectin, including the carbonyl (C=O) group at around 1735 cm-1 an the hydrogel (-OH) group at approximately 3347.94 cm-1 along with other polysaccharide functional groups. These characteristics indicate that the extracted pectin has as hydrogel, which can be applied as adsorbents for water pollutants.